Values and attitude certainty: The case for attitude clarity and correctness - Blankenship, Kevin L.; Kane, Kelly A.; Machacek, Marielle G. (Frontiers in Psychology, 2022)
Three studies examined how the perception that one’s attitudes are based in values affects attitude clarity and correctness. Specifically, perceiving that one’s attitude is based in important values increases attitude clarity (the subjective sense that one knows one’s attitude) but not attitude correctness (the subjective sense that the attitude is correct). To test this, participants read a counterattitudinal message and were given feedback about the basis of their attitude. Relative to participants who learned that their attitudes were weakly based in values, participants who were told that their attitudes were strongly based in values reported greater attitude clarity than correctness (Study 1). Similarly, increases in attitude clarity from having an attitude based in values increased the perception that participants effortfully processed the message (Studies 2 & 3), the belief that participants more successfully resisted the message, and participants’ intentions to act on the attitude.